1994
DOI: 10.1182/blood.v83.2.517.517
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II levels and drug sensitivity in adult acute myelogenous leukemia

Abstract: The topoisomerase (topo) II-directed agents etoposide, daunorubicin (DNR), and amsacrine (m-AMSA) are widely used in the treatment of acute myelogenous leukemia (AML). In the present study, multiple aspects of topo II-mediated drug action were examined in marrows from adult AML patients. Colony-forming assays revealed that the dose of etoposide, DNR, or m-AMSA required to diminish leukemic colony formation by 90% (LD90) varied over a greater than 20-fold range between different pretreatment marrows. Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…In our study, topo IIβ ranged from undetectable levels up to 2.5‐fold in AML cells and 1.1‐fold in CLL cells compared with the CCRF‐CEM control cells. It has been reported by Kaufmann et al (1994) that topo II levels varied widely in clinical specimens from AML patients. Western blot analysis of AML marrow samples revealed that the content of topo II varied more than 20‐fold.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, topo IIβ ranged from undetectable levels up to 2.5‐fold in AML cells and 1.1‐fold in CLL cells compared with the CCRF‐CEM control cells. It has been reported by Kaufmann et al (1994) that topo II levels varied widely in clinical specimens from AML patients. Western blot analysis of AML marrow samples revealed that the content of topo II varied more than 20‐fold.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have shown discrepant results in cell lines and clini- cal samples regarding the topo IIa expression status and cellular susceptibility to topo IIa poison. Although studies in cell lines have suggested that cells with high amounts of this enzyme are more sensitive to the cytotoxicity of topo II inhibitors [24,25], several subsequent studies have demonstrated that the activity of this enzyme in clinical AML samples does not correlate with drug sensitivity in vivo [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive value of topo IIa activity in clinical behavior of AML patients remains a topic of debate. Although most of the available clinical data indicate that the expression of this enzyme does not correlate with drug sensitivity or survival outcome in AML [26][27][28], some suggest otherwise [29]. The actual prognostic role of topo IIa protein in AML needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the mechanisms of action of TAS-103 involve the inhibition of both Topo I and Topo II, and that TAS-103 can be effective against cell lines with already acquired resistance to an inhibitor of Topo. One may expect TAS-103 to show anti-tumor effects in patients when CPT-11 and VP-16 are no longer effective, since it was reported that the resistance of clinical cancers is correlated with a low expression of either Topo, 39) rather than with a mutation of the Topo gene. 40) One of the possible approaches to overcome drug resistance to either Topo I or Topo II inhibitor is combination therapy with a Topo I inhibitor and a Topo II inhibitor.…”
Section: Discussionmentioning
confidence: 99%